THE USE OF PROCESSES AS REFLECTED IN WOMAN PORTRAYALS IN BATAK TOBA SONGS LYRICS - Rita Rasi Uli Sihombing; Sumarsih Sumarsih; Syamsul Bahri (LINGUISTICA, 2017)
The study is concerned with the way the writer explores The Use of Processes as Reflected in Woman Portrayals in Batak Toba Songs Lyrics. How the use processes linguistically represented and the reason of processes realization as it is. The research method used in this paper is qualitative research and based on Halliday Theory use in the types of process. There were 244 clauses of process from the 15 song of Batak Toba. The findings of this research showed that six types of process. it implied that songs in Batak Toba expressed that Mental Process is the dominant type as 38, 6 % from the 94 clauses is found. It implied that the woman portrayals in Batak Toba song expressed what the feel with the sensing which covering thinking, feeling and emotions which happened inside human being. It related to the relational process that cause of the value of woman in the Batak Toba song lyric with the identification of the position woman portrayals. Keywords: Process, Six Types of Processes, Woman Portrayals